2012
DOI: 10.1177/0093650212438097
|View full text |Cite
|
Sign up to set email alerts
|

The Proteus Effect in Dyadic Communication

Abstract: An original experiment explored the differing predictions of the Proteus effect (Yee & Bailenson) and behavioral compensation processes (Bond) in dyadic computer-mediated interaction. The experiment randomly assigned male dyad members to see an attractive, unattractive, or no avatar representation of his female partner, while female dyad members were assigned to see either attractive, unattractive, or no avatar representation of themselves. Results supported the hypothesized behavioral compensation effect such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Star indicates statistical significance < 0.05 against the reference value "4". scores were correlated with Ownership scores (respectively r 0.55, p 0.04 and r 0.67, p < 0.01), which is consistent with the literature (Heide et al, 2013).…”
Section: Proteus Effectsupporting
confidence: 90%
See 3 more Smart Citations
“…Star indicates statistical significance < 0.05 against the reference value "4". scores were correlated with Ownership scores (respectively r 0.55, p 0.04 and r 0.67, p < 0.01), which is consistent with the literature (Heide et al, 2013).…”
Section: Proteus Effectsupporting
confidence: 90%
“…Studies in immersive virtual environments have indicated that there are correlations in avatar attractiveness and reported friendliness (Yee and Bailenson, 2009) which informed our exploration in this domain. Similar research has demonstrated the antithetical effect of negative valence and aggressive reaction (Peña et al, 2009), while our approach was also justified by evidence for manifest behavior changes following avatar based self-concept alteration (Heide et al, 2013), also termed the Proteus Effect (Yee and Rickertsen, 2007).…”
Section: Related Worksupporting
confidence: 52%
See 2 more Smart Citations
“…Customization contributes to self-avatar congruence by allowing customized objects (e.g., avatars) to reflect desired aspects of the user's identity (Franke et al, 2010;Kim and Sundar, 2012). This heightened congruence, enabled via customization, has been shown to positively influence attitudes (Van Der Heide et al, 2013) and overall well-being (Fox et al, 2009).…”
Section: Introductionmentioning
confidence: 99%